PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI MEDIASI (Studi Pada Perusahaan Daerah Air Minum Tirta Dharma Kabupaten Jepara) - Elina Rahma Pratiwi, 14.05.51.0130; Yunianto, Askar (Students Journal of Economic and Management, 2018)
The purpose of this study is to analyze the influence of motivation and work environment on employee performance with job satisfaction as mediation at PDAM Tirta Dharma Jepara. In this study the independent variables that affect employee performance is limited to motivation, work environment with the mediation variable is job satisfaction. The population in this study is the total employee PDAM Tirta Dharma Jepara, amounting to 130 people. And elected as many as 116 respondents are used as a sample. Data testing techniques used include validity test with factor analysis, reliability test with alpha cronbach, multiple regression analysis, and significance test of coefficient of determination to prove the truth of the hypothesis and mediation test. The result of the research shows that the ability of the model to explain correctly the effect of motivation, work environment, and job satisfaction is 64,3% on employee performance. While the other by 35,7% influenced by other variables. From the mediation test can be seen that job satisfaction mediate the influence of motivation and work environment on employee performance.Keywords: motivation, work environment, job satisfaction, and employee performance